Srategi Humas Dalam Membangun Citra Positif Rumah Sakit Jiwa (Prof. Hb. Saanin Padang) Di Pandangan Masyarakat Minang - Fatimah Azzahra; Fatmawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Mental hospitals are synonymous with a negative image in the eyes of society. No exception in the view of the Minangkabau community, West Sumatra in viewing the RSJ (Psychiatric Hospital) Prof. HB. Saanin Padang. The type of research used is the type of field research. The data is carried out by interview surveys and taking sources from various articles on several websites. And as for the case that was raised, it is a case that has actually happened a long time ago and is still happening and there is only one case, namely the case of changing the mindset of the Minangkabau community in responding to Prof. RSJ. HB. Saanin Padang. Minang people still have a negative view of the RSJ which they think is a place for crazy people, a dirty and scary place, then over time this thought is embedded in people's minds so that if they listen to the word mental hospital, they will immediately feel afraid and anxious.